Unhairing animal hides using probiotic Bacteria bacillus subtilis - Данилкович, Анатолій Григорович; Гвоздяк, Петро Ілліч; Романюк, Оксана Олександрівна; Ковтуненко, Ольга Василівна (Eastern-European Journal of Enterprise Technologies, 2013)
The most efficient technology of processing natural raw materials into skin and fur is the use of enzyme products for soaking and liming processes. Therefore, the use of bacterial products, which produce enzymes of various functional effects, is considered to be very promising for the above mentioned processes. Soaking and liming of flint-dried rabbit hides were carried out using probiotic bacreria Bacillus subtilis on 4 samples in a laboratory centrifuge at soaking temperature 36-38°С and working solution рН 6,7-7. Unhairing was made by painting method, except one sample, unhairing of which was made mechanically after having soaked the hides in solution for 36-48 hours. Due to active action of Bacillus subtilis bacteria, the soaking process was reduced, unhairing was conducted without lime-sulfide painting paste, and the period of semi-finished product softening was decreased by 30 minutes. According to chemical analysis data, the concentration of chrome (III) oxide in spent solution is lower, and according to physical-mechanical tests of hides, the hygrothermal stability reaches its maximal value. The obtained results prove the prospects of Bacillus subtilis bacteria use in developing effective technologies of soaking and liming processes of leather and fur production. The technology elaborated allows combining soaking, unhairing, liming and desalting into a one-phase technological process. Advantages of this technology are 2 times faster soaking, comparing to the existing technology, with leather output increased by 20%, and reduction of chromium compounds in spent solutions by 34% that decreases the anthropogenic impact on the environment during its implementation.